PERANCANGAN ALAT UJI GESEKAN ALIRAN DI DALAM SALURAN - Jhon Fitter Siregar; Jorfri B Sinaga (Jurnal Ilmiah Teknik Mesin, 2013)
Mechanical Engineering Department, University of Lampung has been established since 1998 and implementation of the learning process at this Department supported by ten laboratories. One of these laboratory is laboratory of Mechanical fundamental phenomena. But testing equipment available until now in this laboratory is still lacking. In this paper is given, design an analysis of test result of friction flow in channel testing equipment, with channels used are: circle, triangel, square with hydraulic diameter of Dh . Results of testing equipment show relationship between friction factor f and Reynolds number close to the graph on Moody diagram in the textbook of fluid mechanics. That means, this friction flow in channel testing equipment can be used to support laboratory work of mechanical fundamental phenomena in the Mechanical Department Engineering, University of Lampung.Keywords: Design, friction factor, laboratory work, mechanical fundamental phenomena.